Three Dimensional Vero Cell-Platform for Rapid and Sensitive Screening of Shiga-Toxin Producing Escherichia coli - To, Celina Z.; Bhunia, Arun K. (Frontiers in Microbiology, 2019)
Shiga-toxin producing Escherichia coli (STEC) is a serious public health concern. Current Vero cell assay, although sensitive, is lengthy and requires 48-72 h to assess STEC presence in a sample. In this study, we investigated if Vero cells in a three-dimensional (3D) platform would provide improved sensitivity for rapid screening of STEC. Vero cells (epithelial kidney cell line) were grown as a monolayer (2D) or in a collagen-matrix (3D) and exposed to Shiga-toxin (Stx) preparation or STEC cells that were pre-exposed to antibiotics (mitomycin C, ciprofloxacin, or polymyxin B) for toxin induction. Lactate dehydrogenase (LDH) release from Vero cells was used as a biomarker for cytotoxicity. Modified tryptic soy broth (mTSB) as enrichment broth containing mitomycin C (2 µg/ml) or ciprofloxacin (100 ng/ml) significantly induced Shiga-toxin production, which was further confirmed by the dot-immunoblot assay. The 3D Vero platform detected STEC after 6 h post-infection with cytotoxicity values ranging from 33%-79%, which is considerably faster than the traditional 2D platform, when tested with STEC. The cytotoxicity for non- Shiga-toxin producing bacteria, Salmonella, Listeria, Citrobacter, Serratia, and Hafnia was found to be below the cytotoxicity cutoff value of 15%. The detection limit for the 3D Vero cell assay was estimated to be 107 CFU/ml for bacteria and about 32 ng/ml for Stx in 6 h. STEC-inoculated ground beef samples (n=27) resulted in 38-46% cytotoxicity, and the bacterial isolates (n=42) from ground beef samples were further confirmed to be stx1 and stx2 positive in a multiplex PCR yielding a very low false-positive result. This 3D cell-based screening assay relies on mammalian cell pathogen interaction that can complement other molecular techniques for the detection of cell-free Stx or STEC cells from food samples for early detection and prevention.